ANALISIS PENGARUH KURS, EKSPOR, DAN IMPOR TERHADAP CADANGAN DEVISA DI INDONESIA PERIODE TAHUN 1992-2021 - Ananda Pangesti, Dwi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This research aims to analyze the influence of exchange rate, exports, and imports on Indonesia's foreign exchange reserves in the period of 1992-2021. The dependent variable is foreign exchange reserves, whereas the independent variables consist of exchange rate, exports, and imports. The research uses secondary data in time series obtained from Indonesia’s World Bank Data. Data are analyzed with VAR (Vector Auto Regression), those analyzed use E-Views 10 apss by including analysis method, which includes stationary tests, stability tests, optimum lag tests, cointegration tests, VAR estimation tests, Engle Granger causality tests, Impulse Response Function (IRF) tests, and Variance Decomposition (VD) tests. The results of the study show that exchange rate variables have a large influence on foreign exchange reserves, while export and import variables have a small effect on foreign exchange reserves.